2022
DOI: 10.1021/acs.jpca.2c07414
|View full text |Cite
|
Sign up to set email alerts
|

Binding Energy and Diffusion Barrier of Formic Acid on Pd(111)

Abstract: Velocity-resolved kinetics is used to measure the thermal rate of formic acid desorption from Pd(111) between 228 and 273 K for four isotopologues: HCOOH, HCOOD, DCOOH, DCOOD. Upon molecular adsorption, formic acid undergoes decomposition to CO2 and H2 and thermal desorption. To disentangle the contributions of individual processes, we implement a mass-balance-based calibration procedure from which the branching ratio between desorption and decomposition for formic acid is determined. From experimentally deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…[26][27][28][29] The GGA XC functional PBE 30 is employed with the help of the Tkatchenko-Scheffler 31 method to reckon with the van der Waals energycorrections as it was previously found to work well for formic acid adsorption on Pd(111). 32 The optimized lattice constant for the Pd crystal is a 0 = 3.945 Å, which agrees within 1% with the experimental lattice constant. 33 The plane wave energy cut-off is set to 450 eV and partial electronic occupations were modeled with the Methfessel-Paxton (N = 1) smearing scheme 34 with a width of s = 0.1 eV.…”
Section: Computationalsupporting
confidence: 76%
See 1 more Smart Citation
“…[26][27][28][29] The GGA XC functional PBE 30 is employed with the help of the Tkatchenko-Scheffler 31 method to reckon with the van der Waals energycorrections as it was previously found to work well for formic acid adsorption on Pd(111). 32 The optimized lattice constant for the Pd crystal is a 0 = 3.945 Å, which agrees within 1% with the experimental lattice constant. 33 The plane wave energy cut-off is set to 450 eV and partial electronic occupations were modeled with the Methfessel-Paxton (N = 1) smearing scheme 34 with a width of s = 0.1 eV.…”
Section: Computationalsupporting
confidence: 76%
“…For these calculations, we use the PBE exchange correlation energy functional with the TS-dispersion correction because we have shown that it provides a better description of the binding energy of formic acid adsorption on Pd(111) than the PW91 or RPBE-D3 functionals. 32 Further support for this choice is given by the work of Hu and coworkers 43 who compared the performance of different DFT functionals and van der Waals correction schemes for formic acid adsorption on Pt(111) and found that PBE-TS is one of the best performing functionals. Binding energies and geometrical parameters are summarized in the ESI Section S4.…”
Section: Theoretical Calculations Of Formic Acid Decompositionmentioning
confidence: 99%